2015
DOI: 10.1111/ijfs.12806
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and physicochemical properties of dry‐cured neck inoculated with probiotic of Bifidobacterium animalis ssp. lactis BB‐12

Abstract: The effect of inoculum level of Bifidobacterium animalis ssp. lactis BB-12 probiotic strain and ripening period on the quality of dry-cured neck was studied. The microbiological parameters (Enterobacteriaceae, LAB and TVC) and physicochemical attributes (pH value, a w , TBARS index, colour) were determined directly after fermentation at 15°C for 3 weeks, after 6 and 12 months of ripening at 4°C. The highest LAB count and a lower pH value were found in the meat inoculated with probiotic strain at 6.6 log cfu g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…A similar relationship was also confirmed in the BB12, thus suggesting that higher LAB counts corresponded to lower pH values in the samples. These results are consistent with other studies on dry-cured meat products subjected to fermentation using Lactobacillus (Skwarek, Dolatowski, & Kołożyn-Krajewska, 2014) or Bifidobacterium (Libera et al, 2015) as the starter cultures. Other authors found similar pH values: 5.04 in probiotic loins stored for 6 months (Neffe-Skocińska, Jaworska, Kolożyn-Krajewska, Dolatowski, & Jachacz-Jówko, 2015), 5.77 in probiotic neck stored for 6 months (Libera et al, 2015), 5.56 in probiotic hams stored for 5 months (Skwarek et al, 2014) and 5.42 in probiotic loins stored for 4 months (Okoń & Dolatowski, 2014).…”
Section: Physicochemical Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…A similar relationship was also confirmed in the BB12, thus suggesting that higher LAB counts corresponded to lower pH values in the samples. These results are consistent with other studies on dry-cured meat products subjected to fermentation using Lactobacillus (Skwarek, Dolatowski, & Kołożyn-Krajewska, 2014) or Bifidobacterium (Libera et al, 2015) as the starter cultures. Other authors found similar pH values: 5.04 in probiotic loins stored for 6 months (Neffe-Skocińska, Jaworska, Kolożyn-Krajewska, Dolatowski, & Jachacz-Jówko, 2015), 5.77 in probiotic neck stored for 6 months (Libera et al, 2015), 5.56 in probiotic hams stored for 5 months (Skwarek et al, 2014) and 5.42 in probiotic loins stored for 4 months (Okoń & Dolatowski, 2014).…”
Section: Physicochemical Parameterssupporting
confidence: 93%
“…The level of B. animalis ssp. lactis BB12 was from 7.41 after 6 months to 6.15 log CFU/g after 12 months of ageing (Libera et al, 2015), and L. acidophilus Bauer reached a level of 6.82 log CFU/g after 6 months of storage (Jaworska, Neffe, Kołożyn-Krajewska, & Dolatowski, 2011). It is not surprising that loins without the addition of starter cultures presented a relatively high LAB, as LAB are common in the natural microflora of fermented meats (Jaworska et al, 2011).…”
Section: Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the current research confirmed that combined L. acidophilus and L. reuteri had the most significant inhibitory effects against C. jejuni in the fresh and roasted fillets, followed by L. reuteri and L. acidophilus A critical property of probiotic microorganisms is their antagonistic ability against microbial pathogens through competition for exclusion, antibacterial aggregation or development of antibacterial constituents, including organic acids, bacteriocins (especially nisin), and hydrogen peroxide [35]. Numerous synergistic mechanisms have been confirmed for the presence of the natural antimicrobial constituents that are produced by probiotic bacteria (e.g., bacteriocins), using the sequential suppression of a usual biochemical pathway and protective enzymes, combination of cell wall biological compounds, and cell wall active agents to increase the uptake of other antibacterial compounds [36,37].…”
Section: Resultssupporting
confidence: 72%
“…; Libera et al . ). The Lactobacillus acidophilus Bauer strain was selected in earlier studies (grant number: N N312 275435) from five strains of lactic acid bacteria ( Lb.…”
Section: Methodsmentioning
confidence: 97%